SCULPTING SELF IN STRUGGLE: A PERFORMATIVE EXPLORATION OF SHAUNA SINGH BALDWIN'S WHAT THE BODY REMEMBERS - M. K., Anjaly Nair (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Shauna Singh Baldwin's Commonwealth Prize-winning book, What the Body Remembers (2000), explores the harsh realities of the history of partition. Baldwin makes the argument that gender places are socially constructed and assessed through performances, which results in a violation of oneness. By applying Butler’s theory of performativity, the paper examines the voices that have been muted because of a particular tradition. By examining the text through Butler's performativity framework, one can argue that performances fundamentally naturalize gender constructs. The psyche interferes with the internalisation process, which leads to melancholy. Therefore the paper tries to offer a new way of looking at the performance of gender places in a different perspective giving recognition to all the marginalised voices. Indo-Canadian author Shauna Singh Baldwin's first book, What the Body Remembers, explores the terrible realities of partition from the standpoint of the Sikh community. In 1999, the book won her the Commonwealth Pens Prize. It is notorious for describing the violence that followed Partition and for showing how the inflated effect of social-artistic spots on gender places led to violations of mortal freedom. Baldwin's depiction of tortured characters and their disturbed psyches captures the pressure and fermentation of the time. The power dynamics between politics and history, as well as how they're entwined with fornication, are outlined in the book. It also highlights how people — women in particular — come the goat for the insincerity of society.